Crowds and Publics - Dean, Jodi (Stasis, 2017)
The last decade of protests have demonstrated the disruptive force of crowds. When the crowd appears in sites unauthorized by state and capital, it creates a political opening, the possibility for political subjectivation. Unlike the fiction of the public sphere, of that phantom public produced by an ideology of publicity that substitutes the fantasy of a unified field of deliberative processes for the actuality of partisan struggle, the crowd expresses the paradoxical power of the people as political subject. Insistent and opaque, the crowd illuminates attributes of political subjectivity distinctive to the contingent, heterogeneous unity of collectives, attributes missed in mistaken characterizations of the political field as consisting of individuals and operating through procedures of democratic deliberation. Rather than a matter of deliberation, choice, and decision, the politics of crowds manifests as breaks and gaps, in the unpredictability of an exciting cause, as well as through collective courage, directed intensity, and capacities to cohere. This does not mean, however, that the crowd is a political subject. The crowd is the Real that incites the political subject. It’s a necessary but incomplete component of political subjectivity, the disruptive power of self- conscious number as it feels its own force.